Model guaranteed transmission rate providing in WiMAX downlink - Al-Janabi H. D.; Al-Dulaimi A. M.; Abed A. H. (Проблеми телекомунікацій, 2013)
Found that the provision of the required transmission rate of WiMAX can be achieved by solving the problem of frequency resource allocation in the downlink. As a result analyzed by the existing mechanisms of the frequency distribution of resources between subscriber stations in a downlink wireless network, operating using the technology of WiMAX. Based on the identified drawbacks of making a mathematical model the distribution of sub-channels in the network standard, IEEE 802.16, which provides a guaranteed rate subscriber stations in the downlink and submitted by a number of linear constraint equations. The novelty of the model lies in the formulation of the problem the frequency distribution of the resource allocation problem as a sub-channel with a firmly fixed number of subcarriers in each of them. The solution to the optimization problem sub-channel allocation proposed to carry out a multiple objective functions that the available frequency resources in order to allocate a minimum number of sub-channels, the distribution of the available frequency resources in order to allocate a minimum transfer speed of each the subscriber stations, the distribution of the available frequency resources to jointly minimize the number of used sub-channels and a transmission rate allocated to subscriber stations in a downlink. A comparative analysis of the solutions obtained by using different objective functions.
Keywords: WiMAX; sub-channels allocation; mathematical model; objective function; required transmission rate